Impacted foreign body in secondary bronchus: chest percussions during therapeutic bronchoscopy - Razali, Mohd. Sayuti; Ahmad, Fadzil; Raja Lope Ahmad, Raja Ahmad Al'konee (Elsevier, 2009)
We report a case of 1-year 7-month-old boy who presented with impacted peanut in the secondary bronchus. An alternative method of dislodging the impacted foreign body was used in this case with concomitant chest percussions during rigid bronchoscopy. This method helped to dislodge the peanut successfully.